A bibliometric analysis of segmentectomy versus lobectomy for non-small cell lung cancer research (1992–2019). Issue 13 (2nd April 2021) - Xu, Zhiyun; Gao, Xiang; Ren, Binhui; Zhang, Shuai; Xu, Lin
Abstract: Background: This study intends to create a series of scientific maps to quantitatively estimate hot spots and emerging trends in segmentectomy versus lobectomy for non-small cell lung cancer (NSCLC) research with bibliometric methods. Methods: Articles published on segmentectomy versus lobectomy for NSCLC were extracted from the Web of Science Core Collection (WoSCC). Extracted information was analyzed quantitatively using bibliometric analysis by CiteSpace to find hot spots and frontiers in this research area. Results: A total of 362 scientific articles on segmentectomy versus lobectomy for NSCLC were collected, and the annual publication rate increased over time from 1992 to 2019. The leading country and the leading institution were the United States and University of Pittsburgh, respectively. Furthermore, the most prolific researchers were, namely, James D. Luketich, Rodney J. Landreneau, Matthew J. Schuchert, Morihito Okada, and David O. Wilson. The analysis of keywords pointed out that carcinoma, bronchogenic carcinoma, limited resection, segmental resection, and morbidity are hot spots and lymph node dissection, minimally invasive surgery, impact, epidemiology, and high risk are research frontiers in this field. Conclusion: Publications related to segmentectomy versus lobectomy for NSCLC have made great achievements based on bibliometric analysis in recent years. However, further research and global collaboration are still required. Finally, we find that segmentectomy for the treatment of NSCLC is receiving much more attention from researchers globally compared with lobectomy in this research area.